STRATEGI DAKWAH UMAR BIN ABDUL AZIZ DALAM MENANAMKAN NILAI-NILAI PENDIDIKAN ISLAM - Zainal Azman (El-Ghiroh : Jurnal Studi Keislaman, 2017)
Characteristic of Umar bin Abdul Aziz's da'wah is reflected in the amar ma'ruf nahi munkar. Seen from da'wah that he did from himself, family and society. The indicator that can be seen from the characteristics of dakwah Umar bin Abdul Aziz seen from the policy that he did in government that visible from the policy in deciding something form of government done. The values of Islamic education contained in the da'wah of Umar bin Abdul Aziz is reflected in the attitude shown by what he did. Attitude in leading the people of justice and wisdom. Besides the values of Islamic education contained in the da'wah Umar bin Abdul Aziz also seen from his personality.